Drugs in development for treatment of patients with cancer-related anorexia and cachexia syndrome [Retraction] - Mantovani G; Madeddu C; Macciò A (Dove Medical Press, 2013)
The Editor-in-Chief, Dr Pilch, of Drug Design, Development and Therapy has been alerted to unacceptable levels of duplication between a previously published paper: Macciò A, Madeddu C, Mantovani G. Current pharmacotherapy options for cancer anorexia and cachexia. Expert Opin. Pharmacotherapy 2012 13(17) 2453–2472 and one published subsequently in Drug Design, Development and Therapy: Mantovani G, Madeddu C, Macciò A. Drugs in development for treatment of patients with cancer-related anorexia and cachexia syndrome. Drug Design, Development and Therapy 2013:7 645–656.